Stabilizability and controllability of systems associated to linear skew-product semiflows - Megan, Mihail; Sasu, Adina Luminita; Sasu, Bogdan (Revista Matemática Complutense, 2002)
This paper is concerned with systems with control whose state evolution is described by linear skew-product semiflows. The connection between uniform exponential stability of a linear skewproduct semiflow and the stabilizability of the associated system is presented. The relationship between the concepts of exact controllability and complete stabilizability of general control systems is studied. Some results due to Clark, Latushkin, Montgomery- Smith, Randolph, Megan, Zabczyk and Przyluski are generalized.